PENJADWALAN DINAS PERAWAT BERHUBUNGAN DENGAN KEPUASAN PASIEN DI RUANG RAWAT INAP RSUD ULIN BANJARMASIN - Rahman, Syawalludin; Mulyani, Yeni; Rizany, Ichsan (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2018)
Patient satisfaction during hospitalization is still in low category. The low patient satisfaction isinfluenced by several factors, one of which is the scheduling of nurse service. This study wasmade to know the correlation between scheduling of nurse service and patient satisfication levelat RSUD Ulin Banjarmasin hospital. This research used correlation design with cross sectionalapproach and accidental sampling technique. Research respondents amounted to 92 people.December 2017 research period and measuring instruments used in the form of questionnaires.The result of the analysis shows that there is a positive relationship between scheduling of nursesservice that is perceived by patient with patient satisfaction level in ward of RSUD UlinBanjarmasin. (P Value = 0,000 <0.05). Suggestion of this research is expected to head of roomand nurse to cooperate in determining good service scheduling with manager direction for thecreation of optimal service for patient satisfaction.